Analysis of the Social Dynamics of Minority Groups Through Biological Behavior Models - Vasileva, Evgeniya (Research Papers, 2021)
The purpose of this article is to analyze whether and how social institutions could imitate biological mechanisms. The assumption is that both types of systems are complicated and can be put under a single denominator, which states that the analogies are not mechanical. This research applies the principles of interaction, structuring of quantities and self-establishment, typical for evolutionary complex systems, to the social dynamics and the construction of identity in minority groups in the Balkans. The article is not intended to be framed only in the field of biology alone, but rather seeks to expand and enrich the transitional field of connections between the biological and the social. The ant colony was used as a prototype of a biological system. The minority groups included in the research are Slavic in ethnicity and Muslims as religious denomination from several Balkan countries. In order to achieve the purpose of the analysis, first, the ways to structure quantities are considered, as the basis of the assumption for comparability between biological and social interaction. Second, the mechanisms for the interaction of an ant colony type of system are discussed. Third, these mechanisms and characteristics are compared to the dynamics and characteristics of the minority groups in the Balkans. Finally, the strengths and limitations of such analysis are outlined as well as an assessment of the applicability of the biological models to social interactions is made.